Timing Is Everything: Changing Norms of Minority Rights and the Making of a Polish Nation-State. (September 2016) - Cramsey, Sarah A.; Wittenberg, Jason
There is broad agreement that states seeking to nationalize their minority populations require both capacity and intent. We argue that political opportunity is also important through a focus on Poland's policy toward its Ukrainian minority during the first half of the twentieth century. The shift from international norms protecting minority group rights in the interwar period to the defense of individual human rights during the immediate postwar era gave Polish state elites new and devastating tools with which to create a Polish nation-state. Through forced expulsions, internal deportation, and the cultural homogenization of the public sphere, all practices that had been unfeasible during the interwar group rights era, Polish state elites denied Ukrainians sufficient means to perpetuate their culture. The postwar process was relatively quick and almost always brutal.